Kondisi Sosial Ekonomi Dan Lingkungan Masyarakat Sebelum Dan Sesudah Pembangunan Pasar Di Nagari Talaok Kecamatan Bayang Kabupaten Pesisir Selatan - Mardani, Mela; Juita, Erna; Zuriyani, Elvi (STKIP PGRI Sumbar, 2013)
Trading activity is exchange goods voluntarily, in the trade market plays a role in supporting the smooth distribution of goods and services. The governments development aims to improve peoples lives in order to achieve prosperity and the establishment of social interaction between people, but in addition there are several market development of environmental problems arising from trading activities. This study aims to obtain data and information are: 1) social interaction before and after the construction market. 2) the level of income before and after the construction market. 3) environmental conditions before and after construction of the market.This research is descriptive, which became the study population are people who are in Nagari Talaok which consists of two villages, namely Kampung Talaok and KampungÂ Lubuk Â Pasiang. Samples were taken proportional random sampling, which took a random sample of 20% with the proportion that the number of respondents in this study amounted to 126 households. Sample respondents are heads of households who are in Nagari Talaok that have direct and indirect activities with market activities in Nagari Talaok kecamatan Bayang.Results of this study found: 1) social interaction before and after the construction market in Nagari Talaok in view of the interaction between traders, the interaction between the family and the interactions between traders or with people in everyday life is generally pretty good. 2) The income level of the community (in view of the expenditure) spending on food and non-food for one month prior to the development of both markets (Rp.1.000.000 â Rp.1.350.000), whereas after the construction market in general is very good (>Rp. 1,350,000), thus it can be said that the villagers income Talaok after the construction market in general has increased and is at the standard minimum wage to the average monthly range between >Rp.1.350.000. 3) Environmental conditions before and after the construction market in Nagari Talaok in view of environmental hygiene, environmental safety and order environment in everyday life is generally good.Â